DEFENSE MECHANISM OF JACOB BLACK REFLECTED IN DAVID SLADE'S ECLIPSE MOVIE (2010): A PSYCHOANALYTIC APPROACH - SETYANINGRUM , ARDHITA (2011)
The research is proposed to analyze the defense mechanism in a movie with the title Eclipse with a Psychoanalytic Approach. There are two objectives: the first is to analyze the movie based on its structural element and to identify the film script based on psychoanalytic perspective by Sigmund Freud. The benefits of this study are to give in the application of Psychoanalytic approach in literary study. The primary data is taken from the video and script of Eclipse movie, while the secondary data is taken from book and the information related to theory of psychology. The method of collecting data is library research. The technique of analyzing data is descriptive. In this study, the writer draws two conclusions. First, based on the structural analysis, it is clear that in this movie, David Slade conveys a message that everyone has to adapt and cooperate each other in spite of different of ego. It can be seen both the natural enemies (vampires and werewolves) are able to cooperate with the same purpose, to protect Bella from bad vampires. In this movie, he adapted the real character Jacob Black who is a werewolf from Quileute clan and stubborn person who is optimist to get Bella's love. Secondly, the researcher concludes that the structural elements in a movie are inseparable. They are related to each other and build a solid unity. The analysis through the structure of psychoanalysis of Freud's Psychoanalytic is connected to each other. From this story the researcher can conclude that the use of ego defense mechanism gives strength to Jacob to face his problems.